2010
DOI: 10.1095/biolreprod.109.078774
|View full text |Cite
|
Sign up to set email alerts
|

The Estrous Cycle of the Ewe Is Resistant to Disruption by Repeated, Acute Psychosocial Stress1

Abstract: Five experiments were conducted to test the hypothesis that psychosocial stress interferes with the estrous cycle of sheep. In experiment 1, ewes were repeatedly isolated during the follicular phase. Timing, amplitude, and duration of the preovulatory luteinizing hormone (LH) surge were not affected. In experiment 2, follicular-phase ewes were subjected twice to a "layered stress" paradigm consisting of sequential, hourly application of isolation, restraint, blindfold, and predator cues. This reduced the LH pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…This study also found that ewes subjected to a variety of acute stressors during the follicular phase, such as food denial, unfamiliar noises, exercise and transportation, had no effect on the LH surge (Wagenmaker et al 2010). There was no difference in the mean latent period to the LH surge in the stressed ewes compared with the control ewes of this study (Wagenmaker et al 2010). This suggests that the type or intensity of the acute stressor may determine the effect of reproductive dysfunction in sheep; however, it contradicts the effects of transportation stress on the preovulatory LH surge observed in other research.…”
Section: Acute Stressmentioning
confidence: 49%
See 3 more Smart Citations
“…This study also found that ewes subjected to a variety of acute stressors during the follicular phase, such as food denial, unfamiliar noises, exercise and transportation, had no effect on the LH surge (Wagenmaker et al 2010). There was no difference in the mean latent period to the LH surge in the stressed ewes compared with the control ewes of this study (Wagenmaker et al 2010). This suggests that the type or intensity of the acute stressor may determine the effect of reproductive dysfunction in sheep; however, it contradicts the effects of transportation stress on the preovulatory LH surge observed in other research.…”
Section: Acute Stressmentioning
confidence: 49%
“…However, both acute and chronic stress-like levels of cortisol had no effect on sexual attractivity and proceptivity behaviours in this study (Papargiris et al 2011). On the contrary, another study found that the repeated exposure of ewes to acute psychosocial stressors over two oestrous cycles did not alter the incidence, timing, amplitude or duration of the preovulatory LH surge (Wagenmaker et al 2010). This study also found that ewes subjected to a variety of acute stressors during the follicular phase, such as food denial, unfamiliar noises, exercise and transportation, had no effect on the LH surge (Wagenmaker et al 2010).…”
Section: Acute Stressmentioning
confidence: 94%
See 2 more Smart Citations
“…There have been many studies in a range of species to show that various stressors interfere with the LH surge and these have been extensively reviewed (Dobson & Smith 2000, Smith & Dobson 2002, Tilbrook et al 2002, Turner et al 2002a, 2005, Breen & Karsch 2006b, Dobson et al 2012. These stressors include (1) transportation that delays or attenuates the LH surge in sheep and cows (Dobson 1987, Nanda et al 1990, Dobson et al 1999, (2) injection of insulin that delayed the LH surge in ewes (Saifullizam et al 2010), (3) metabolic stress caused by caloric restriction that can disrupt and stop oestrous cycles in ewes (Wagenmaker et al 2010), (4) restraint that can block the preovulatory surge in rats (Roozendaal et al 1997a,b) and (5) immune/inflammatory stress that suppresses pulsatile LH secretion during the preovulatory period in sheep (Battaglia et al 2000) and delays or blocks the LH surge in follicular phase ewes, cows and monkeys (Peter et al 1989, Xiao et al 1998, Battaglia et al 2000. With respect to immune stress, endotoxin was shown to disrupt the oestradiol-induced LH surge in ovariectomized ewes by interfering with the early activating effects of the oestradiol signal (Battaglia et al 1999) and by acting centrally to suppress the secretion of GNRH (Breen et al 2004a).…”
Section: Role Of Cortisol In Influencing the Impact Of Stress On Surgmentioning
confidence: 99%